2016
DOI: 10.1002/chem.201602173
|View full text |Cite
|
Sign up to set email alerts
|

Highly Facet‐Dependent Photocatalytic Properties of Cu2O Crystals Established through the Formation of Au‐Decorated Cu2O Heterostructures

Abstract: This work confirms the presence of a large facet-dependent photocatalytic activity of Cu2 O crystals through sparse deposition of gold particles on Cu2 O cubes, octahedra, and rhombic dodecahedra. Au-decorated Cu2 O rhombic dodecahedra and octahedra showed greatly enhanced photodegradation rates of methyl orange resulting from a better separation of the photogenerated electrons and holes, with the rhombic dodecahedra giving the best efficiency. Au-Cu2 O core-shell rhombic dodecahedra also displayed a better ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
107
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 43 publications
(106 reference statements)
6
107
0
3
Order By: Relevance
“…Theo bserved large facet-dependent photocatalytic properties of polyhedral Cu 2 O, TiO 2 ,a nd other semiconductors can be similarly explained, as the efficiency of photoexcited charge migration to external surfaces or heterojunctions strongly depends on the contacting faces. [7][8][9][10][11][12][13] Furthermore,this thin layer with dissimilar band structures for different surface planes also gives rise to the observed facet-dependent optical absorption and emission properties in semiconductor nanocrystals and quantum nanostructures that has been recognized recently. [13][14][15][16][17][18] Since facet effects are observable in many semiconductor materials,i ti s highly interesting to examine possible existence of facetdependent electrical properties of silicon.…”
mentioning
confidence: 89%
“…Theo bserved large facet-dependent photocatalytic properties of polyhedral Cu 2 O, TiO 2 ,a nd other semiconductors can be similarly explained, as the efficiency of photoexcited charge migration to external surfaces or heterojunctions strongly depends on the contacting faces. [7][8][9][10][11][12][13] Furthermore,this thin layer with dissimilar band structures for different surface planes also gives rise to the observed facet-dependent optical absorption and emission properties in semiconductor nanocrystals and quantum nanostructures that has been recognized recently. [13][14][15][16][17][18] Since facet effects are observable in many semiconductor materials,i ti s highly interesting to examine possible existence of facetdependent electrical properties of silicon.…”
mentioning
confidence: 89%
“…This model is also very useful to explain widely observed facet-dependent photocatalytic properties of many semiconductor materials and heterostructures, in which photocatalytic activities can vary from highly active to completely suppressed depending on the exposed or contacting facets as seen in Cu 2 Oc rystals and Cu 2 O-ZnOh eterostructures. [9][10][11][12][13][14][15] As the ultrathin layer has dissimilar band structures for different crystal faces it meanst hat light of somewhat differentw avelengths is absorbed by particles of variouss hapes, accounting for the observedf acet-dependent opticalp roperties of Cu 2 Oa nd other semiconductor crystals. [7,11,[16][17][18] To verify that the facet-dependent electrical-conductivity phenomenon is broadly observable in semiconductors, electrical-conductivity measurementsh ave been made on four different faces of Si wafers, which revealed that the (111)a nd (112) surfaces are highly conductive.…”
Section: Introductionmentioning
confidence: 99%
“…Successful syntheses of popular Cu 2 O nanocubes, octahedra, rhombic dodecahedra, and other polyhedral shapes have greatly advanced our knowledge of semiconductor nanocrystals by showing their electrical conductivity, photocatalytic activity, optical absorption, and heat transmission properties are strongly depended on the exposed surface facets . The observations of these unusual properties are not accidental and entirely unexpected, but nature led us to discover these material properties because they are all related manifestation of facet effects semiconductor nanocrystals possess.…”
Section: Introductionmentioning
confidence: 99%
“…The observations of these unusual properties are not accidental and entirely unexpected, but nature led us to discover these material properties because they are all related manifestation of facet effects semiconductor nanocrystals possess. These facet‐dependent phenomena can be explained in terms of the presence of a thin surface layer having different degrees of band bending or different band structures for various surfaces . Although still not being widely recognized, facet‐dependent electrical, photocatalytic, and optical properties have been observed in other semiconductor nano‐ and microcrystals including TiO 2 , Ag 2 O, PbS, and Ag 3 PO 4 .…”
Section: Introductionmentioning
confidence: 99%